(untitled) - Stead, Rebecca (New York, 2009)
In the 1980s, as her mother prepares to be a contestant on a television game show, Miranda tries to make sense of a series of mysterious notes received from an anonymous source that seems to defy the laws of time and space.
Newbery Award, 2010
Keywords: Space and time; Fiction; New York (N.Y.); Fiction; History; 20th century